External Capital Analysis on Sustainability of MSMEs Led by Women - Hana Fauzia; Alfiah Hasanah (JEJAK: Jurnal Ekonomi dan Kebijakan, 2022)
Micro small and medium enterprises (MSMEs) led by women have many challenges to confront continue to exist. Various external capitals come with advantages and disadvantages. The investigation looks at the business sustainability of MSMEs led by women by comparing banks or non-banking institutions as the source of the main capital as the main independent variables as well as other variables such as employee, characteristics of female entrepreneur; age, education, marriage status, participation in arisan, household characteristics ; asset, size, young children and elderly member. The data from Indonesian Family Life Survey (IFLS) 2014 is used and probit estimation is applied. The result shows that women led MSMEs are more likely to sustained the business as much as 1.8 percentage points if they start the business from informal financial institutions/friends/family (non-banking) as a source of funding compared to women led MSMEs that start the funding from bank institutions. Estimations results also show that factors such as age, education, participation in arisan, household size, and employee also positive and significantly contribute to the business survival of women led MSMEs. However, other factors such as married status, household assets, and having children, are negatively contribute to the business survival of women led MSMEs.